2019
DOI: 10.3389/fimmu.2019.01191
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation by Mesenchymal Stem Cells (MSCs): Mechanisms of Action of Living, Apoptotic, and Dead MSCs

Abstract: Expectations on mesenchymal stem cell (MSC) treatment are high, especially in the fields of sepsis, transplant medicine, and autoimmune diseases. Various pre-clinical studies have been conducted with encouraging results, although the mechanisms of action behind the observed immunomodulatory capacity of mesenchymal stem cells have not been fully understood. Previous studies have demonstrated that the immunomodulatory effect of MSCs is communicated via MSC-secreted cytokines and has been proven to rely on the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
449
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 556 publications
(469 citation statements)
references
References 109 publications
12
449
0
8
Order By: Relevance
“…These ndings emphasize the importance of apoptosis in MSC-mediated immunomodulation and might explain previous study results, in which apoptotic MSCs (apoMSCs) were shown to be superior compared to living MSCs [8][9][10]. Besides, numerous studies recently revealed that apoptotic cells release not only apoptotic bodies but also a range of extracellular vesicles (Evs) that can act as biological modulators.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…These ndings emphasize the importance of apoptosis in MSC-mediated immunomodulation and might explain previous study results, in which apoptotic MSCs (apoMSCs) were shown to be superior compared to living MSCs [8][9][10]. Besides, numerous studies recently revealed that apoptotic cells release not only apoptotic bodies but also a range of extracellular vesicles (Evs) that can act as biological modulators.…”
supporting
confidence: 64%
“…MSCs have no active cell metabolism, it can be assumed that they do not differentiate into CAF-like cells with the corresponding secretion of growth factors, cytokines, and chemokines [6,10]. Notably, dead…”
mentioning
confidence: 99%
“…We revealed that only MSCs are able to suppress the granzyme B‐mediated cytotoxic CD8 + T‐cell response, which is known as one of the principal mediators of acute allograft rejection . MSCs have been shown to suppress T‐cell proliferation and shift the effector functions of T‐cells toward regulatory functions, mainly through the expression of immunomodulatory molecules such as IDO, and secretion of prostaglandin‐E2 (PGE2), nitric oxide, and TGF‐ÎČ . Lacking metabolic and secretory activity, HI‐MSCs have no T‐cell suppressive effect, which makes them incapable of prolonging allograft survival in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Proposed interaction of MSCs with host immune cells and released cytocines; Data obtained from[33,34], The figure is made with biorender (https://biorender. com/)…”
mentioning
confidence: 99%